EFFECT OF PRUNNING PATTERN AND SOIL MULCHING ON YIELD AND QUALITY OF KEITT MANGO IN NEW RECLAIMED LANDS - B. Salama; A. Abou-Hadid; N. Abdelhamid; M. El-Shinawy (Arab Universities Journal of Agricultural Sciences, 2018)
The present study was carried out during 2014 and 2015 seasons on adult Kitt Mango Trees to evaluate 4 levels of pruning  pattern (removing one-third, one-half, all branch or without pruning) and 4 types of soil mulching (white plastic, black plastic, rice straw or without soil mulching) on vegetative growth, leaf mineral content ,flowering and yield. Average shoot length, shoot thickness and average number of shoot / tree of Kitt mangos greatly affected with both pruning pattern and soil mulching, especially with removing of one-third of branch and covering soil with white plastic sheet. However leaf N, P and K contents were improved with both one-third and one-half pruning of branches of Kitt mango trees where both white and black plastic of mulch soil were similar in their effect on leaf NPK content. There were an evident increase in fruit set %, total yield (kg/tree) and marketable yield % with one-third and one-half pruning of branch and also with white and black plastic of soil mulching. The increase of marketable yield% due to these treatments could be attributed to the increase of vegetative canopy of leaves which led to prevent sun burn of fruits and to minimize heat solar effect from the soil and protect the fruits in lower parts of the trees. Fruit chemical constituents including TSS%, acidity and L-ascorbic acid slightly affected with different treatments but one-third and one-half prunning of branch as well as with white and black plastic of soil mulch could be recommended as a good horticulture treatments in Kitt mango orchards